2021
DOI: 10.1016/j.apenergy.2021.116565
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the COVID-19 lockdown on energy consumption in a Canadian social housing building

Abstract: The COVID-19 pandemic hit societies in full force in 2020 and compelled people all around the world to change their lifestyle. The time spent at home significantly surged during the pandemic and this change in occupancy can have a direct impact on building energy consumption. COVID-19 lockdowns also accelerated the transition towards telework, a trend that many expect to last. Changes in energy consumption under lockdown is thus a valuable asset to forecast how energy could be consumed in buildings in the futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
87
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 20 publications
11
87
1
1
Order By: Relevance
“…Another study reviewed the total electricity demand for several different locations, sectorial electricity demand, and residential electricity demand patterns which showed an overall decrease in total electricity demand, but up to a 30% increase in the residential sector. Through analyzing the average electricity loads for housing units with rooftop solar, analysis identifies an increase in electricity use during daytime hours when there is higher occupancy [ 22 ]. While these studies provide insight into residential energy use for before and during the pandemic, there are limitations in the quantification of these changes in electricity use for a typical housing unit, in addition to understanding how residential buildings continued to be impacted during the several months following the initial lockdown period.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reviewed the total electricity demand for several different locations, sectorial electricity demand, and residential electricity demand patterns which showed an overall decrease in total electricity demand, but up to a 30% increase in the residential sector. Through analyzing the average electricity loads for housing units with rooftop solar, analysis identifies an increase in electricity use during daytime hours when there is higher occupancy [ 22 ]. While these studies provide insight into residential energy use for before and during the pandemic, there are limitations in the quantification of these changes in electricity use for a typical housing unit, in addition to understanding how residential buildings continued to be impacted during the several months following the initial lockdown period.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic hit the world in earnest in 2020 and has since changed the way of life of people worldwide (Mckinsey 2020;Rouleau and Gosselin 2021). Specifically, social distancing has become the norm in most countries to prevent the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Homes have suddenly become places for living, sleeping, cooking, working, studying, and keeping fit, with the possibility (and need) of using appliances at any time. Thus, total energy consumption has changed, affecting energy consumption at a large scale such as in districts or municipalities [23][24][25][26], or counties [27,28], and at a small scale (e.g., homes), as also proven by questionnaire surveys [29] and monitoring [30].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in [30], the authors found that lockdown measures influenced electric and hot water consumption and use, when the most intensive lockdown measures were applied, impacting consumer energy bills and how energy utilities might have been solicited during the pandemic.…”
Section: Introductionmentioning
confidence: 99%